Documenting the advantages and limitations of different classes of molecular markers in a well-established phylogeographic context: lessons from the Iberian endemic Golden-striped salamander, Chioglossa lusitanica (Caudata: Salamandridae) - Sequeira, Fernando; Alexandrino, Joao [UNESP]; Weiss, Steven; Ferrand, Nuno (Blackwell Publishing, 2008)
Previous analyses of mitochondrial (mt)DNA and allozymes covering the range of the Iberian endemic golden-striped salamander, Chioglossa lusitanica, suggested a Pleistocene split of the historical species distribution into two population units (north and south of the Mondego river), postglacial expansion into the northernmost extant range, and secondary contact with neutral diffusion of genes close to the Mondego river. We extended analysis of molecular variation over the species range using seven microsatellite loci and the nuclear P-fibrinogen intron 7 (beta-fibint7). Both microsatellites and beta-fibint7 showed moderate to high levels of population structure, concordant with patterns detected with mtDNA and allozymes; and a general pattern of isolation-by-distance, contrasting the marked differentiation of two population groups suggested by mtDNA and allozymes. Bayesian multilocus analyses showed contrasting results as populations north and south of the Douro river were clearly differentiated based on microsatellites, whereas allozymes revealed differentiation north and south of the Mondego river. Additionally, decreased microsatellite variability in the north supported the hypothesis of postglacial colonization of this region. The well-documented evolutionary history of C. lusitanica, provides an excellent framework within which the advantages and limitations of different classes of markers can be evaluated in defining patterns of population substructure and inferring evolutionary processes across distinct spatio-temporal scales. The present study serves as a cautionary note for investigations that rely on a single type of molecular marker, especially when the organism under study exhibits a widespread distribution and complex natural history. (C) 2008 The Linnean Society of London, Biological Journal of the Linnean Society, 2008, 95, 371-387.
Keywords: allozymes; beta-fibrinogen gene; evolutionary history; microsatellites; mtDNA; nuclear genealogy